How Might We Screen for Psychological Factors in People With Pelvic Pain? An e-Delphi Study. Issue 4 (3rd February 2021) - Pontifex, Angela; Savin, Caris; Park, Caitlin; Nunes, Alina Filipe; Chalmers, K Jane; Neumann, Patricia B; Ng, Leo; Thompson, Judith A
Abstract: Objective: Persistent pelvic pain (PPP) is a complex condition often influenced by psychological factors that can alter treatment outcomes. These factors are potentially modifiable; however, currently there is no instrument to screen for them. The purpose of this study was to determine: (1) which psychological factors should be screened in individuals with PPP, and (2) the most appropriate statements to represent these psychological factors. Methods: The study used a focus group design followed by an electronic-Delphi (e-Delphi) process. A focus group consisting of 8 experts was conducted to determine the relevant psychological factors to screen. These results informed round 1 of the e-Delphi process, consisting of a panel of 14 pain/pelvic pain experts. The e-Delphi process consisted of 3 rounds of online surveys and 2 teleconference discussions to establish consensus on the most appropriate statement to screen for each of the psychological factors. Results: The focus group identified 13 relevant psychological factors. During the e-Delphi process, relevant screening statements were assessed using a 100-point allocation system. Experts could reword and suggest new statements. Statements were assessed for consensus and stability and were eliminated as the rounds progressed if they met the exclusion criteria. At the termination of round 3, there were 15 statements remaining. Conclusion: The final list of 15 statements will assist clinicians in screening for psychological factors and is an important step for clinicians in providing psychologically informed care to people with PPP. Future research should determine the psychometric properties of the statements to determine their clinical utility as a questionnaire. Impact: This study has refined a list of statements to help screen for psychological factors in individuals with PPP. Developed robustly using an e-Delphi method, this list is an important first step forward for clinicians to provide psychologically informed care to these individuals.